DOP29 The Normalization and Transition of J-Pouch Phenotype in the Chicago Classification of Pouchitis. (27th May 2021) - Akiyama, S; Cohen, N; Traboulsi, C; Rai, V; Glick, L; Yi, Y; Runde, J; Cohen, R; Skowron, K; Hurst, R; Umanskiy, K; Shogan, B; et al.
Abstract: Background: Pouchitis can develop in up to 70% of patients with inflammatory bowel disease (IBD) treated by proctocolectomy with ileal pouch-anal anastomosis (IPAA). In our recent work, we proposed the "Chicago classification of pouchitis" describing 7 main pouch phenotypes with differing outcomes. In this study, we assessed the transition of pouch phenotypes in our classification. Methods: This is a retrospective study of IBD patients with IPAA who subsequently underwent pouchoscopies at the University of Chicago between June 1997 and December 2019. We reviewed all available reports of pouchoscopies after ileostomy takedown and classified the pouches into 7 main phenotypes: (a) normal, (b) afferent limb (AL) involvement, (c) inlet (IL) involvement, (d) diffuse, (e) focal inflammation of the pouch body, (f) cuffitis, and (g) pouch fistulas (Figure 1). A normal pouch was defined as a pouch without any abnormal findings including fistulas. AL, IL involvement, and cuffitis were defined as any type of endoscopic inflammation in the AL, IL, and rectal cuff, respectively. Diffuse inflammation was defined as two or more endoscopic inflammatory findings in all anatomical locations of the pouch body (the tip, proximal, and distal pouch). Focal inflammation was defined as pouchitis that did not meet the criteria for diffuse inflammation. Pouch fistulas included pouches with any type of fistulas noted ≥6 months from ileostomy takedown. Using a Kaplan-Meier curve, event-free survival (EFS) was assessed from the scope date when a primary phenotype was first identified to the date when a subsequent phenotype was described. We excluded patients if a subsequent phenotype was identified before or at the scope date when a primary phenotype was initially noted. Logistic regression analysis was performed with variables with a P -value <0.05 in a Fisher's exact test. Results: We reviewed 1, 359 pouchoscopies from 426 patients (90% preoperative diagnosis of ulcerative colitis). The most common subsequent inflammatory phenotype was focal inflammation (55%-88%), followed by IL involvement (31%-67%), cuffitis (33%-46%), diffuse inflammation (20%-38%), AL involvement (21%-32%), and pouch with fistulas (9%-20%). The rate of subsequent normal pouch was 6%-25% with pouch fistulas having the lowest normalization rate (6%, 5-year EFS 93%) (Table 1, Figure 2). On multivariable analysis, pouch fistulas were negatively associated with pouch normalization (OR 0.17, 95% CI 0.06–0.48) (Table 2). Conclusion: We demonstrated that pouch phenotype can change over time and pouch normalization is possible. Further studies are needed to determine if pouch normalization should be a goal of treatment for IBD patients with IPAA.